Masalah Mental Remaja di Kota Semarang - Fitri Hartanto; Hendriani Selina (MEDIA MEDIKA INDONESIANA, 2010)
Adolescent mental problems in the city of Semarang Background: The gap between the child's physical, social and psychological in adolescence can cause mental problems in the form of emotional disturbance, behavior, resistant and depression. No data on the distribution of mental problems among adolescents in Semarang.Methods: Descriptive study with cross sectional approach conducted on 578 Junior High School Students who are spread in 5 Junior High School in Semarang. SDQ (the strength and difficulties questionnaire) measure tool were used in assessing their mental status, which is presented in a descriptive narrative.Results: In the domain of prosocial are 8.0% abnormal and 14.5% borderline, hyperactive domain are 4.9% abnormal and 5.9% borderline, emotional domain are 18.5% abnormal and 9.1% borderline, the domain of behavior are 13.9% abnormal and 15.7% borderline, and the domain of peer group are 3.8% abnormal and 20.6% borderline.Conclusion: The result of the assessment of mental problems adolescents in Semarang got emotional problems 18.5%, behavior 13.9%, the total difficulties 9.1%, 8.1% prosocial, hyperactivity 4.9%, and peer group 3.8%.ABSTRAKLatar belakang: Kesenjangan yang terjadi antara perkembangan fisik, sosial dan psikologik pada masa remaja dapat menyebabkan masalah mental berupa gangguan emosi, perilaku, serta depresi. Belum ada data tentang distribusi masalah mental pada remaja di Kota Semarang.Metode: Penelitian deskriptif dengan pendekatan belah lintang dilakukan terhadap 578 pelajar SLTP yang tersebar pada 5 SLTP di wilayah Semarang. Alat ukur SDQ (the strength and difficulties questionnaire) dipakai dalam menilai status mental mereka yang disajikan dalam narasi deskriptif. Hasil: Pada ranah prososial didapatkan 8,0% abnormal dan 14,5% borderline, ranah hiperaktif 4,9% abnormal dan 5,9% borderline, ranah emosi 18,5% abnormal dan 9,1% borderline, ranah perilaku 13,9% abnormal dan 15,7% borderline, dan ranah peer group 3,8% abnormal dan 20,6% borderline. Simpulan: Hasil penilaian masalah mental remaja di Kota Semarang didapatkan masalah emosi 18,5%, perilaku 13,9%, total difficulties 9,1%, prososial 8,1%, hiperaktif 4,9%, dan peer group 3,8%.